Corrigendum to ‘Ethanolysis Pre-treatment of Crude Palm Oil in High Shear Reactor’ [agriTECH, (2025), 45, 1, 10.22146/agritech.81499] - Hidrotunnisa, Hidrotunnisa; Yanti, Rini; Hidayat, Chusnul (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
DOI of original article: https://doi.org/10.22146/agritech.81499Authors Correction:The authors regret a typographical error in the ABSTARCT page 41. It was written as 'yielding FAEE 1358±16 ppm and TCC 99.9±0.2%'. It should correctly read 'yielding FAEE 99.9±0.2% and TCC 1358±16 ppm'.